Supporting User Awareness Using Smart Device-Based Notifications - López Herrera, Gustavo (2016)
This paper provides an overview of a doctoral research project which focuses in developing a framework to allow smart device-based notifications to provide user awareness. Notifications are mechanisms by which the user’s atten‐ tion is driven to specific tasks or events. Notifications should provide a balance between intrusiveness and value in order to avoid annoyed users. The results reported in this paper include 50 % of the overall results expected for the project. The first step was to conduct a systematic literature review assessing the use of smart devices to deliver notifications, the second step was the development of a framework to allow notification coordination among smart devices and the third result is a laboratory case study assessing the framework. Future work includes two case studies in real scenarios and further analysis of usage patterns identified during this research.